Clinical, Economic And Humanistic Evaluation Of A Worksite Health Promotion Program Conducted Among Employees Of A Public University In Malaysia - Liau, Siow Yen (2011)
The burden of cardiovascular (CV) diseases is increasing in Malaysia. This has an adverse effect on the country’s health, society and economy. The general objective of this research was to develop an effective and efficient worksite health promotion program that could reduce the cardiovascular risk factors among employees at the Universiti Sains Malaysia (USM) Engineering campus. This was a quasiexperimental study conducted between 2009 and 2010. The six-month program consisted of individualized counseling and seminars targeted at five behavioral risk factors (RFs) i.e. smoking, alcohol consumption, inadequate fruit and vegetable intake, physical inactivity and overweight/obesity.